2018
DOI: 10.1002/smll.201803639
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/NiS Yolk–Shell Microsphere‐Based Electrodes for Overall Water Splitting and Asymmetric Supercapacitor

Abstract: Rational designing of the composition and structure of electrode material is of great significance for achieving highly efficient energy storage and conversion in electrochemical energy devices. Herein, MoS2/NiS yolk–shell microspheres are successfully synthesized via a facile ionic liquid‐assisted one‐step hydrothermal method. With the favorable interface effect and hollow structure, the electrodes assembled with MoS2/NiS hybrid microspheres present remarkably enhanced electrochemical performance for both ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(121 citation statements)
references
References 77 publications
7
113
1
Order By: Relevance
“…Then, we scratched the MoS 2 and NiS 2 powders from the carbon cloth, then mechanically mixed MoS 2 and NiS 2 with the atomic ratio of Mo:Ni = 1:1 (denoted as MoS 2 -NiS 2 ). [50,52,53] Consequently, these results further demonstrate the effect of the interface, which could enrich the active sites and promote the electronic transfer, and thus boost the sluggish water splitting efficiency. As shown in Figure S15 in the Supporting Information, it can be found that MoS 2 /NiS 2 shows much better HER and OER performances than that of mechanically mixed MoS 2 -NiS 2 sample.…”
mentioning
confidence: 63%
“…Then, we scratched the MoS 2 and NiS 2 powders from the carbon cloth, then mechanically mixed MoS 2 and NiS 2 with the atomic ratio of Mo:Ni = 1:1 (denoted as MoS 2 -NiS 2 ). [50,52,53] Consequently, these results further demonstrate the effect of the interface, which could enrich the active sites and promote the electronic transfer, and thus boost the sluggish water splitting efficiency. As shown in Figure S15 in the Supporting Information, it can be found that MoS 2 /NiS 2 shows much better HER and OER performances than that of mechanically mixed MoS 2 -NiS 2 sample.…”
mentioning
confidence: 63%
“…The Tafel slope of NiCoFe‐PS nanorod/NF is better than those of IrO 2 based catalyst (97.8 mV dec −1 ), accounting for the fast kinetic process. In contrast, the performance of NiCoFe‐PS nanorod/NF is one of the best among reported catalysts for OER in Figure c …”
Section: Resultsmentioning
confidence: 90%
“…Specifically, well‐regulated nanostructures not only improve the utilization of active materials, but also shorten the diffusion path of ions, thereby promoting the reaction kinetics of the electrodes and improving electrochemical performance . For example, Qin et al synthesized MoS 2 /NiS egg yolk‐shell microsphere structure, the specific capacitance at a current density of 0.2 A g −1 is 1493 F g −1 . Subramanian et al prepared NiS/CoS/PEDOT on a foamed nickel substrate by chemical bath deposition, showing a specific capacitance of 353 F g −1 at a current density of 15 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%